Prevalence of Aeromonas spp. Infection in Pediatric Patients Hospitalized with Gastroenteritis in Latvia between 2020 and 2021 - Irina Grave; Aleksandra Rudzate; Anda Nagle; Edvins Miklasevics; Dace Gardovska (MDPI AG, 2022)
Purpose: Aeromonas species are emerging human enteric pathogens. However, there is no systematic analysis of Aeromonas infection in the pediatric population in Latvia. The aim of the study was to describe potential sources, prevalence of infection, associated virulence factors and antimicrobial resistance of Aeromonas spp. isolated from fecal samples. Methods: Stool samples (n = 1360) were obtained from the Children's Clinical University Hospital between 2020 and 2021. The target population was pediatric patients, 0 to 18 years of age, with a preliminary diagnosis of gastroenteritis. Identification was performed by Maldi-TOF, antimicrobial resistance by Vitek2 and 9 virulence factors by polymerase chain reaction (PCR). Results: Aeromonas spp. were isolated in 50 stool samples; positive findings made up 3.6% of all study cases and included four species: A. hydrophila, A. caviae, A. veronii, and A. eucrenophila. In 42% of the samples, Aeromonas spp. appeared alongside the other significant pathogens: Campylobacter jejuni, Salmonella Enteritidis, Salmonella Typhimurium, Yersinia enterocolitica, norovirus, adenovirus, and rotavirus. The study population positive for Aeromonas spp. infection contained 28 male (56%) and 22 female (44%) patients; median age was 4.56 years. The most common symptoms were: diarrhea, blood in stool, vomiting, abdominal pain, and fever. Aside from expected natural resistance, no significant antibacterial resistance was detected. The presence of multiple virulence genes was noticed in all isolates. No statistically significant correlation was found between the virulence patterns, bacterial species, and the intensity of clinical symptoms. Discussion: According to the clinical data and the results of this study Aeromonas spp. has an important role in pediatric practice and requires appropriate attention and monitoring.